2015
DOI: 10.1080/09540121.2014.993352
|View full text |Cite
|
Sign up to set email alerts
|

Kganya Motsha Adolescent Centre: a model for adolescent friendly HIV management and reproductive health for adolescents in Soweto, South Africa

Abstract: This paper reports on Kganya Motsha Adolescent Centre, an adolescent program specifically established to provide voluntary counseling and testing as well as management of HIV-positive young people in Soweto, South Africa. A retrospective cross-sectional analysis, using clinic records of young people accessing services from 2008 to 2012, was conducted. Of the 11,522 who tested, 7689 (67%) were females. The total number of HIV infections was 410, with an HIV prevalence of 3.6% (95% CI 3.2-3.9%). More females (33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Soweto is a large township southwest of Johannesburg with a population of approximately 1.3 million predominantly (98.5%) black inhabitants residing in informal and formal settlements [32]. While there are no population-level statistics on HIV prevalence among adolescents in Soweto, a recent study of 11,552 adolescents and young adults (14–25 years) residing in Soweto, reported that 4% of those who accessed HIV testing services at a local youth-centered clinic tested positive for HIV, including 2% of young men 4% of young women [33]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soweto is a large township southwest of Johannesburg with a population of approximately 1.3 million predominantly (98.5%) black inhabitants residing in informal and formal settlements [32]. While there are no population-level statistics on HIV prevalence among adolescents in Soweto, a recent study of 11,552 adolescents and young adults (14–25 years) residing in Soweto, reported that 4% of those who accessed HIV testing services at a local youth-centered clinic tested positive for HIV, including 2% of young men 4% of young women [33]. …”
Section: Methodsmentioning
confidence: 99%
“…KMAC was opened in 2008 with a local mandate to address HIV and sexual and reproductive health priorities of adolescents (ages 14–19 years). Earlier pilot studies on adolescent health identified the urgent need for such youth-centred services, and informed the development and implementation of BBAHS [3336]. …”
Section: Methodsmentioning
confidence: 99%
“…Loss to follow-up during the period between positive HIV testing and linkage to care, delayed initiation of antiretroviral therapy (ART), and poor levels of early retention in care significantly contribute to high HIV-related morbidity and mortality globally among adolescents and youth [8,1014]. Addressing these challenges is particularly important during the initial stage following a new diagnosis of HIV in adolescents and youth, a time when successful initiation into the HIV care cascade may improve long-term outcomes and decrease HIV transmission among these key populations.…”
Section: Introductionmentioning
confidence: 99%
“…While advocating for and strengthening HTC uptake and coverage, linkage to quality care should be available to make HTC ultimately beneficial. Recent studies have cited early loss-to-follow-up, refusal of care, and nonreceipt of baseline CD4 as barriers to engagement in care among newly-identified ALHIV (68)(69)(70). We recommend the following measures to create an enabling environment for HTC among adolescents, including those at highest risk:…”
Section: Enabling Strategies and Interventions To Improve Adolescent mentioning
confidence: 99%